Phosphorylation of Plant Microtubule-Associated Proteins During Cell Division - Vavrdová, Tereza; ˇSamaj, Jozef; Komis, George (Frontiers in Plant Science, 2019)
Progression of mitosis and cytokinesis depends on the reorganization of cytoskeleton, with microtubules driving the segregation of chromosomes and their partitioning to two daughter cells. In dividing plant cells, microtubules undergo global reorganization throughout mitosis and cytokinesis and with the aid of various microtubule associated proteins (MAPs) they form unique systems such as the preprophase band (PPB), the acentrosomal mitotic spindle and the phragmoplast. Such proteins include nucleators of de novo microtubule formation, plus end binding proteins involved in the regulation of microtubule dynamics, crosslinking proteins underlying microtubule bundle formation and members of the kinesin superfamily with microtubule-dependent motor activities. The coordinated function of such proteins not only drives the continuous remodeling of microtubules during mitosis and cytokinesis, but also assists the positioning of the PPB, the mitotic spindle and the phragmoplast, affecting tissue patterning by controlling cell division plane (CDP) orientation. The affinity and the function of such proteins is variably regulated by reversible phosphorylation of serine and threonine residues within the microtubule binding domain through a number of protein kinases and phosphatases which are differentially involved throughout cell division. The purpose of the present review is to provide an overview of the function of protein kinases and protein phosphatases involved in cell division regulation and to identify cytoskeletal substrates relevant to the progression of mitosis and cytokinesis and the regulation of CDP orientation.